OP0150 Paradoxical effect of biological dmards in rheumatoid arthritis patients with overweight and obesity: less often clinical remission, but also less radiological damage. (15th June 2017) - Jonge, AV de; Wee, MM ter; Bultink, IE; Lems, WF
Abstract : Background: The relationship between treatment with biological disease-modifying antirheumatic drugs (DMARDs), including TNF-blocking agents, and disease activity in overweight and obese rheumatoid arthritis (RA) patients has not been clarified yet. Objectives: The aim of this review is to assess the effect of overweight/obesity on the therapeutic efficacy of these drugs. Secondly, we aimed to assess the influence of overweight/obesity on the occurrence of joint destruction. Methods: A systematic review of all articles published on these subjects using PubMed and EMBASE was executed. For the first research question, studies were eligible when focused on the clinical efficacy of biological DMARDs only in overweight/obese RA patients versus patients with normal body weight. For the second research question studies were eligible when questioning the relation between overweight and joint destruction in patients with RA. Overweight and obesity were defined according to the following body mass index (BMI) categories; BMI <20 kg/m 2 for underweight, BMI 20–25 kg/m 2 for normal weight, BMI 25–30 kg/m 2 and BMI >30 kg/m 2 for overweight. Results: A total of 6782 articles were found, of which 12 were eligible for this review. A total of 3647 RA patients were treated with adalimumab, etanercept, infliximab, golimumab, or certolizumab pegol, or TNF blockers, rituximab, or tocilizumab. Ten studies used disease activity as outcome. In general, these studies showed that higher BMI is associated with poor response, based on either outcome or percentages on remission or improvement defined according to EULAR guidelines. In addition, four studies showed that higher BMI is also associated with higher Health Assessment Questionnaire (HAQ)-scores. Two articles (of which one article described the results of studies in two different RA cohorts) focused on the association between BMI and joint destruction. These articles showed that higher BMI values were associated with lower odds for having joint destruction. One study also showed that having a BMI <20 kg/m 2 was associated with a higher odds ratio (OR =4.12) for joint destruction. Conclusions: Higher BMI levels in RA patients treated with biological DMARDs are associated with reduced therapeutic efficacy as compared to RA patients with normal body composition. The unfavourable effect of body weight on disease activity was paralleled by a favourable, protective effect on joint destruction. This uncoupling is not fully elucidated yet, and should be further investigated. Disclosure of Interest: None declared